Monogenic Diabetes in a Family with 2 unknown HNF-4A Gene Mutations - Motzkau, M.; Meyer, P.; Mertens, P.R.; Klose, S. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Diabetes mellitus classified as Maturity Onset Diabetes of the Young (MODY) is characterized by autosomal dominant inheritance with insulin secretory disturbances.In 2 siblings with diabetes mellitus manifestation at age under 25 years, low fasting glucose levels, severely elevated glucose levels upon glucose challenge and absent autoantibodies for IA2 and GAD clarification for MODY was sought. Mutational screening for MODY 1–3 mutations was carried out by direct sequencing followed by multiplex ligation-dependent probe amplification (MLPA).We identified a mutation within the hepatic nuclear factor 4A (HNF-4A) gene hitherto unreported for MODY-1. A causative role of the mutation is not proven, however in the 2 index patients similar phenotypes are present. These cases underline the necessity to screen for MODY when the medical history and lack of autoantibodies suggest alternative diagnoses beside type 1 diabetes.
Keywords: diabetes; Maturity Onset Diabetes of the Young; insulin secretory disturbances; hepatic nuclear factor 4A